2013
DOI: 10.1002/asia.201300780
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Redox‐Active Liquid Crystals Composed of Tetraazanaphthacene Derivatives

Abstract: Liquid‐crystalline (LC)­ N‐heteroacenes, tetraazanaphthacene (TANC), and fluoflavin (FFV) were synthesized, and their self‐assembly into columnar LC structures at room temperature was investigated. LC TANC and LC FFV functioned as an electron acceptor and electron donor, respectively. A TANC/FFV LC mixture showed ESR activity in the presence of a strong base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Unlike fluorescent π‐conjugated liquids such as anthrathene, carbazole, and OPV derivatives reported by some groups,,,, N‐heteroacene‐based π‐conjugated liquid itself can show various fluorescent colors by responding to external stimuli as proton. N‐Heteroacene, in which some electron‐deficient imino‐N atoms is substituted instead of C atoms in a polyaromatic hydrocarbon, has much attracted attentions as electron acceptors and n‐type semiconductors . Also, an imino‐N atom has lone pair electrons characteristic of Lewis basic feature on sp 2 ‐hybridized orbital and is capable of interacting with Lewis acid such as proton and metal ions.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Unlike fluorescent π‐conjugated liquids such as anthrathene, carbazole, and OPV derivatives reported by some groups,,,, N‐heteroacene‐based π‐conjugated liquid itself can show various fluorescent colors by responding to external stimuli as proton. N‐Heteroacene, in which some electron‐deficient imino‐N atoms is substituted instead of C atoms in a polyaromatic hydrocarbon, has much attracted attentions as electron acceptors and n‐type semiconductors . Also, an imino‐N atom has lone pair electrons characteristic of Lewis basic feature on sp 2 ‐hybridized orbital and is capable of interacting with Lewis acid such as proton and metal ions.…”
Section: Figurementioning
confidence: 99%
“…Since Kim et al . have reported that the melting point of two methoxy‐substituted derivative is 147–148 °C, a introduction of two branched long alkoxy chains is very effective to reduce the intermolecular interaction between rigid π‐conjugated frameworks, of which behavior is consistent with previous reports for N‐heteroacene derivatives . Also, the X‐ray diffraction (XRD) measurement of coated film for 1 at room temperature also displayed no peak, which imply that 1 does not form ordered structure in a condensed state, but adapt an isotropic liquid state in Figure a.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The groups of Bunz and Miao have reported the fabrication of n ‐type semiconductors in crystal states and the preparation of larger heteroacenes linearly substituted with triisopropyl (TISP) ethynyl groups . Recently, some groups have reported a series of liquid‐crystalline (LC) N ‐heteroacene derivatives self‐organizing into ordered superstructures such as 1‐demensional (1D) columnar and 2‐dimensional (2D) lamellar LC phases via non‐covalent intermolecular interactions . These thin films for lamellar LC structures can transport charge carriers such as electrons and holes through π – π stacking between π‐conjugated frameworks.…”
Section: Figurementioning
confidence: 99%
“…The introduction of two long racemic alkoxy chains to the π‐conjugated framework confers high solubility in various organic solvents, which can be easy to prepare as drop‐cast films. The dibenzophenazine derivative was prepared according to previous procedures (see the Supporting Information) . Unfortunately, 1 exhibited no mesomorphism, as confirmed by polarized optical microscopic observations (see Figure S1).…”
Section: Figurementioning
confidence: 99%